Artificial Intelligence in Public Information Systems: Transforming Digital Governance and Service Delivery - Tienne Nhung (Asian Digital Governance Problems, 2025)
Purpose: This study examines how Artificial Intelligence (AI) contributes to the transformation of public information systems, digital governance, and public service delivery in Vietnam while identifying the institutional factors that support sustainable AI adoption. Subjects and Methods: A qualitative case study approach was employed involving government officials, public information system managers, information technology specialists, and citizens with experience using AI-enabled public services. Data were collected through semi-structured interviews, document analysis, and literature review, and analyzed using thematic analysis. Results: The findings indicate that AI has significantly improved administrative efficiency through service automation, chatbot technology, machine learning, and integrated digital information systems. AI strengthened transparency, accountability, evidence-based decision making, and citizen-centered service delivery by improving accessibility, response speed, and service consistency. However, the study also identified persistent challenges, including unequal digital infrastructure, limited human resource capacity, regulatory adaptation, cybersecurity, data governance, and institutional coordination. These findings demonstrate that successful AI implementation requires organizational and governance transformation alongside technological innovation. Conclusions: AI has become a strategic enabler of digital transformation in Vietnam by enhancing public information systems and governance performance. Nevertheless, the sustainability of AI adoption depends on balanced investments in technological capability, institutional readiness, regulatory support, human capital development, and collaborative governance to ensure transparent, accountable, inclusive, and responsive public administration.